Formulasi dan Evaluasi Lip cream Halal Menggunakan Ekstrak Tomat (Lycopersicon esculentum Mill) Sebagai Pewarna Alami - QOSIM, ABDUL (Jurnal Farmasi Udayana; Vol. 12, No 1, Tahun 2023DO - 10.24843/JFU.2023.v12.i01.p06, 2023)
Abstract — Lip cream is a semi-solid to liquid textured preparation that functions as a lip dye. Tomato plants can be used as natural dyes because they contain lycopene compounds which can give a yellow to red color. This study aims to determine whether tomato fruit extract can be formulated as a dye, determine the effect of adding tomato extract concentration and determine the halal critical point in the preparation of tomato fruit extract lip cream as a natural dye. The tomato fruit extraction method was carried out using UAE with methanol solvent. The resulting extract was then added to each formula with concentrations of F0 (0%), F1 (5%), F2 (10%) and F3 (15%). The organoleptic test results showed that all formulas had a semi-solid texture, smelled of roses and F0 was white, F1 was light orange, F2 was orange and F3 was brick red. All formulas comply with the homogeneity and pH test standards as indicated by the pH value range of 6.47 - 5.17. All formulas had good smearing power, adhesion of ?60 seconds and spreadability test values ??ranging from 5.90 to 5.63. The results of the ANOVA analysis on the pH and spreadability tests showed that the preparations had significant differences between the formulas. Evaluation of halal critical points on preparations does not have halal critical points in terms of materials and processing.